2018
DOI: 10.1186/s13075-018-1733-6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the capillaroscopic skin ulcer risk index in systemic sclerosis patients in clinical practice: a longitudinal, multicentre study

Abstract: BackgroundNailfold capillaroscopy (NC) is an important tool for the diagnosis of systemic sclerosis (SSc). The capillaroscopic skin ulcer risk index (CSURI) was suggested to identify patients at risk of developing digital ulcers (DUs). This study aims to assess the reliability of the CSURI across assessors, the CSURI change during follow-up and the value of the CSURI in predicting new DUs.MethodsThis multicentre, longitudinal study included SSc patients with a history of DUs. NC images of all eight fingers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…First, CSURI was developed, which identifies patients at risk of developing new DU in a 3-month follow-up [3][4][5]. However, a multicentre study showed that 40% of their patients were not assessable with CSURI due to the absence of megacapillaries, which are an essential part of the index's equation [6]. Furthermore, Caramaschi et al developed a score of risk factors that was associated with ischemic digital ulcers in SSc patients undergoing Iloprost treatment.…”
Section: Introductionmentioning
confidence: 99%
“…First, CSURI was developed, which identifies patients at risk of developing new DU in a 3-month follow-up [3][4][5]. However, a multicentre study showed that 40% of their patients were not assessable with CSURI due to the absence of megacapillaries, which are an essential part of the index's equation [6]. Furthermore, Caramaschi et al developed a score of risk factors that was associated with ischemic digital ulcers in SSc patients undergoing Iloprost treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Für die SSc wurde der „capillaroscopic skin ulcer risk index“ als prognostischer Verlaufsscore entwickelt und validiert, konnte sich aber in multizentrischen Studien nicht bestätigen lassen [ 10 , 11 , 12 ]. Die Kapillardichte (in Kapillaren/mm Nagelfalz) bleibt wichtigster prognostischer Marker [ 13 , 14 , 15 ].…”
Section: Befundung Und Scoringunclassified
“…Wartość CSURI obliczana jest na podstawie kilku czyn- ników: liczby kapilar w dystalnym rzędzie w obrębie wału paznokciowego oraz liczby i najszerszego wymiaru megakapilar w ocenie kapilaroskopowej. W niedawnych badaniach autorzy zakwestionowali jednak wartość prognostyczną indeksu CSURI ze względu na ryzyko błędów związanych z samym badaniem oraz stosowanymi metodami analizy statystycznej [14].…”
Section: Nailfold Capillaroscopyunclassified